P06.11 The impact of periodic presumptive treatment for vaginal infections on the vaginal microbiome among women participating in the preventing vaginal infections trial. (13th September 2015) - Balkus, JE; Andac, C; Fredricks, DN; Anzala, O; Kimani, J; Schwebke, J; Srinivasan, S; Lee, J; McClelland, RS
Abstract : Background: A randomised trial of monthly periodic presumptive treatment (PPT) with intravaginal metronidazole 750 mg plus miconazole 200 mg reduced bacterial vaginosis (BV) by 35% compared to placebo. We further assessed the effect of the intervention on detection of select bacterial species in the vaginal microbiome. Methods: HIV-uninfected, non-pregnant women aged 18–45 years from the US and Kenya were randomised to receive PPT or matching placebo for 5 consecutive nights each month for 12 months. Vaginal fluid specimens were collected every other month using Dacron swabs and tested using species-specific quantitative PCR assays that target the 16S rRNA gene. Relative risks [RR] were generated using generalised estimating equations with a log link and exchangeable correlation structure to separately assess the effect of the intervention on species detection. Results: Of 234 women enrolled, 221 (94%) had specimens for analysis (PPT n = 110; placebo n = 111). The proportion of follow-up visits with individual species detected was lower in the PPT arm versus placebo for: BVAB1 (13.8% vs. 23.7%; RR = 0.60, 95% CI 0.39–0.93), BVAB2 (30.7% vs. 42.5%; RR = 0.72; 95% CI 0.55–0.95), BVAB3 (22.9% vs. 31.0%; RR = 0.75, 95% CI 0.54–1.03), Atopobium vaginae (59.7% vs. 72.7%; RR = 0.82, 95% CI 0.71–0.94), Leptotrichia/Sneathia (49.4% vs. 60.6%; RR = 0.81, 95% CI 0.68–0.97), and Megasphaera species (26.8% vs. 43.8%; RR = 0.61, 95% CI 0.46–0.82). Lactobactillus crispatus and L. jensenii were more frequently detected in the PPT arm (L. crispatus: 31.8% vs. 26.7%, p = 0.19; L. jensenii: 31.8% vs. 25.1%; p = 0.07). However, these increases were not statistically significant. The prevalence of Gardnerella vaginalis and L. iners during follow-up was high (90% and 91%, respectively) and did not differ by arm. Conclusions: Use of monthly PPT for one year significantly reduced BV prevalence as well as colonisation with a number of bacterial species strongly associated with BV. The role of PPT to improve vaginal health should be considered. Disclosure of interest statement: R. S. M. has received honoraria for invited lectures and consulting as well as donated study product for this trial from Embil Pharmaceutical Company. R. S. M. currently receives research funding from Hologic/Gen-Probe. J. E. B. received honoraria from Symbiomix, Inc for consulting and donated reagents from Hologic/Gen-Probe. J. S. has received consultancy payments from Akesis, Hologic, Symbiomix, and Starpharma, and has grants/pending grants from Akesis, BD Diagnostic, Hologic, Cepheid, Quidel, Symbiomix, Starpharma, and Viamet. All other authors declare that they do not have a commercial or other association that might pose a conflict of interest.